Mary McCarthy. - Stock, Irvin, 1920- (University of Minnesota pamphlets on American writers ;, 1968)
Mary McCarthy - American Writers 72 was first published in 1968. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.